The q-tensor square and the group νq (G) for some families of finite p-groups, q ≥ 0 - Gonçalves, Nathália Nogueira (2021)
Tese (doutorado)—Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Matemática, 2021.